Cinetics: Fueling Entrepreneurial Innovations through Crowdfunding. Issue 2 (November 2016) - Li, Zhuoxin; Jarvenpaa, Sirkka L.; Pattan, Nisha
The case examines how the founder of a startup company came up with the entrepreneurial idea and used Kickstarter as a platform to establish and grow his company. The case describes in detail the history of the company and charts out the crowdfunding campaigns that provided the company the initial funding. The case concludes at the point at which the founder is considering different funding options to scale the company even further. The case can be used in a variety of classes including digital business, open innovation, strategic IT management, digital innovation and entrepreneurship, and digital marketing.